Licenciatura em Educação do Campo do Instituto Federal de Educação, Ciência e Tecnologia do Pará: estudos sobre sua organização curricular - Duarte, Adalcilena Helena Café (2017)
The aim of this dissertation is to identify the pertinent elements to the curricular organization of the Field Education Degree developed at the Federal Institute of Education, Science and Technology of Pará (IFPA), in view of the teachers' training process, the practices developed in the spaces / times of their pedagogical formative itineraries and the construction of policies aimed at an emancipatory education of the subjects of the field. In order to do so, it focuses its studies on the subject of curricular organization based on the curriculum of the Degree in Field Education course on IFPA. The investigative process is anchored in the qualitative research of the case study type, with two stages: a semi-structured interview with the management of the course and followed by the analysis of documents, more specifically the Pedagogical Project of the course (PPC ) And evaluation reports of the learners-educators on the community time. This study is based on the contributions of authors, specialists and researchers focused on pertinent issues. They are: Ramos (2004), Hage (2005), Gimeno Sacristán (2013). Moreira and Candau (2003), Frigotto (2006), Goodson (2013), Hamilton (1992), Freire (2005), Lopes and Macedo (2011), Apple (2006), Torres Santomé 2008), Silva (1999), Morin (2003), Arroyo (2006), Japiassú (1976), Ciavatta (2005), Nosella (2004), Gadotti (2004), Bernstein (1981), Thiesen and Oliveira Try curriculum; Caldart (2004, 2008), Caldart et al (2012), Hage (2014), Baptista (2003), Santos (2012), Arroyo (1999), Kolling (1999), Hage and Cruz (2015) Molina e Sá ), Molina (2015) to deal with Field Education; Chizzotti (2014) to deal with public-private issues. Through the analysis of the data collected, the results of the research are identified as the categories: Pedagogical alternation, curricular Integration and dialogue between knowledge, beyond the units of analysis, constitute the structuring pillars of the course that provide a democratic political character of inclusion of the voices of the subjects of the curriculum and the subjects of the field. In addition, the curriculum of the course, thought as a continuous process of construction effectively needs the intervention of curricular subjects aware of their role as protagonists of a new reality of Field Education